Nuclear incoherent photoproduction of π0 and η from 4 to 12 GeV - Rodrigues, T. E.; Arruda-Neto, J. D.T.; Mesa, J. [UNESP]; Garcia, C.; Shtejer, K.; Dale, D.; Nakagawa, I.; Cole, P. L. (American Physical Society (APS), 2010)
The mechanism of incoherent π0 and η photoproduction from complex nuclei is investigated from 4 to 12 GeV with an extended version of the multicollisional Monte Carlo (MCMC) intranuclear cascade model. The calculations take into account the elementary photoproduction amplitudes via a Regge model and the nuclear effects of photon shadowing, Pauli blocking, and meson-nucleus final-state interactions. The results for π0 photoproduction reproduced for the first time the magnitude and energy dependence of the measured rations σγA/σγN for several nuclei (Be, C, Al, Cu, Ag, and Pb) from a Cornell experiment. The results for η photoproduction fitted the inelastic background in Cornell's yields remarkably well, which is clearly not isotropic as previously considered in Cornell's analysis. With this constraint for the background, the η→γγ decay width was extracted using the Primakoff method, combining Be and Cu data [Γη→γ γ=0.476(62) keV] and using Be data only [Γη→γγ= 0.512(90) keV]; where the errors are only statistical. These results are in sharp contrast (~50-60%) with the value reported by the Cornell group [Γη→γγ=0.324(46) keV] and in line with the Particle Data Group average of 0.510(26) keV. © 2010 The American Physical Society.